Corporate Social Responsibility, Corporate Life Cycle, and Dividend Policy - Eman Abdel-Wanis (Journal of Accounting, Business and Management (JABM), 2020)
The aim of this paper is to investigate the impact of corporate social responsibility(CSR) on dividend policy through corporate life cycle (CLC) as a mediator using pathanalysis for 308 firms-observation for 80 non-financial firms during the period from 2014to 2017 using smart PLS (partial least square). This paper explores the impact of the socialresponsibility on the dividends policy and explores the role of each life cycle in this effecton dividends. The results show that firms in their growth stage are positively associatedwith CSR, while firms in stage of decline are less likely to invest in CSR. High CSR firmsmay use dividend policy to reduce the agency problems related to overinvestment in CSR.Results refer to corporate life cycle isn't influenced by dividends. The results show thatcorporate life cycles play an important role in enhance the relationship CSR and dividendpolicy especially in the growth stage in in the Egyptian business environment